The Effect of Polymer on Triglyceride Microemulsion Formulation for Tertiary Oil Recovery - Jeirani, Z.; Mohamed Jan, B.; Noor, I.M.; See, C.H.; Saphanuchart, W. (American Chemical Society, 2013)
This paper presents the effect of polymer on the rheological properties of triglyceride microemulsions. Non-Newtonian shear thinning behavior of triglyceride microemulsions has been modeled satisfactorily using a power law. It was observed that the effects of surfactant and cosurfactant concentrations on the apparent viscosity are significant. However, the effect of salinity on the same viscosity is very trivial. Viscosities of the tested samples have shown a tendency to increase significantly with the addition of xanthan gum (high molecular weight exocellular polysaccharide). The increase is affected by the function of temperature and polymer concentrations, mainly influencing the terminal relaxation time of the solutions. This way, the optimum polymer concentration, 1500 ppm, was obtained on the basis of the performance of the optimum thickened triglyceride microemulsion in tertiary oil recovery at various temperatures and polymer concentrations.